Digital tools in the blended learning process in Peruvian Dental Education during the COVID-19 Pandemic. - Blanco-García, Luz Elvira (2022)
The COVID-19 pandemic has generated a pedagogical vacuum in dental education, which, due to the clinical, practical and laboratory nature of the subjects, forced teachers to incorporate innovative digital teaching resources in which learning environments are simulated that help promote the development of skills and knowledge in search of continuous improvement. However, students have also seen the need to resort to virtual platforms that allow them to better adapt to this complex hybrid blended learning system. The findings of this review are the product of an exploratory study whose purpose was to identify the main Information and Communication Technologies and organize them according to interpretation tools, dynamic modeling; communication, collaboration and organization. In this way, we provide the academic community with a vision of their impact on the learning and self-learning process, their experiences of use and the perception of the benefits and limitations of these new technologies in a current context in Dentistry students. In the first part we address the state of the art on the pedagogical components of ICT, the role they play in higher education, the characteristics and standards they must meet to become cognitive tools allied to formal education, so that Allow the interaction and knowledge management of the students.Next, we share the results of an open survey of undergraduate students of a Peruvian School of Dentistry that was carried out as a preliminary diagnostic phase that became the starting point for the validation of instruments of a research work on experiences of the use of the ICT as digital and cognitive tools for teaching and learning in online dental education that has study code No. 0209 of the Research Ethics Committee of the Faculty of Medicine of the Universidad Nacional Mayor de San Marcos; The responses obtained show the resources at the service of their formal and scientific skills related to users’ own skills called “digital natives” motivating them to be the protagonists of their learning and development of skills for adequate professional performance.